THE ROLE OF KANAFIA TELZHANOV’S CREATIVITY IN THE CONTEXT OF THE SPIRITUAL AND PATRIOTIC EDUCATION OF YOUNG ARTISTS OF KAZAKHSTAN - Mukhametkalina N.T.,; Seitakhmetova N.L., (Academic Journal of Physical and Chemical Sciences, 2020)
. In the modern world, which is subject of the processes of globalization, standardization, national original cultural aspects, the social significance of art in the spiritual and moral education of the young generation of Kazakhstani artists is very relevant and quite important. The works of one of the first Kazakh painters Kanafia Telzhanov are the sources of the revival of spirituality, so necessary for the modern society. One of the aspects of Kanafia Telzhanov’s originality of his artistic vision is the unique color palette, which is the living reflection on the color of folk art, created artistic images that fully reveal the spiritual traditions of the nation. Reflecting the history, mental coloristic features, specifics of imaginative and coloristic thinking of Kazakhs, it expresses the essence of the national identity. This will serve as the means of aesthetic and spiritual education of young artists. The process of forming the national identity of young artists is impossible without the influence of traditional artistic images that feed the artist with new means of expression. Kanafia Telzhanov’s creativity is preserved in the consciousness of the modern society as an example for the younger generation to follow them very actively.